Benign tumors of the heart: myxoma of the right atrium – A case report - Hinić, Saša; Šarić, Jelena; Milojević, Predrag; Gavrilović, Jelena; Durmić, Tijana; Ninković, Nebojša; Milovanović, Branislav; Djoković, Aleksandra; Mićović, Slobodan; Tomović, Milosav; Zdravković, Marija (Vojnosanitetski pregled, 2020)
Introduction. Myxoma is the most common primary benign heart tumor. The most frequent location is the left atrium, the chamber of the heart that receives oxygen-rich blood from the lungs. Myxomas usually develop in women, typically between the ages of 40 and 60. Symptoms may occur at any time, but most often they are asymptomatic or oligosymptomatic for a long period of time. Symptoms usually go along with body position, and are related to compression of the heart cavities, embolization and the appearance of general symptoms. The diagnosis of benign tumors of the heart is based on anamnesis, clinical features and findings of the tumor masses by use of non-invasive and invasive imaging methods. Extensive surgical resection of the myxoma is curative with minimal mortality. Long term clinical and echocardiographic follow-up is mandatory. Case report. We reported a case of a 62-year-old male, presented with 15 days of intermittent shortness of breath, dizziness and feeling of heart palpitations and subsequently diagnosed with right atrial myxoma based on transthoracic echocardiography . The patient was emergently operated in our hospital. Long-term follow-up did not reveal recurrence. Conclusion. Our case was an atypical localisation of right atrial myxoma. Whether the intracardiac mass is benign or malignant, early surgery is obligatory in order to prevent complications.
Keywords: myxoma; heart neoplasms; diagnosis; echocardiography; echocardiography, transesophageal; histological techniques; cardiac surgical procedures; treatment outcome.